'Mr. Clean' and his 'computer boys': technology, technocracy, and de-politicisation in the Indian National Congress (1981–1991). Issue 1 (2nd January 2022) - Sharma, Amogh Dhar
ABSTRACT: The trajectory of the Indian National Congress is often narrated as one of progressive and terminal decline. This article focuses on a largely neglected period in the history of the INC from the 1980s when the party was subject to techno-managerial reforms intended to revitalise the party. Launched under Rajiv Gandhi, this modernisation project entailed the use of large-scale data collection, computerisation, and technocrats for managing intra-party affairs. By exploring the interface between technology and politics, this article demonstrates the impact that the reforms had on India's political culture and helps contextualise contemporary processes of intra-party organisational change.